Genealogi Pengajaran Islam dan Nasionalisme Agama KH. Zaini Mun’im dan KHR. As’ad Syamsul Arifin - Amrozi, Shoni Rahmatullah; Maskuri, Maskuri; Renaningtyas, Peni Catur (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2020)
Abstract: A thing that makes a difference between intellectual traditions of pesantren and other education, namely the existence of sanad. In the perspective of Ibn Qayyim Al-Jauzy, sanad called exceeding the exotological linearity of Islamic knowledge which is called 'ilm al-jally. Moreover, Imam Syafi'i said that the people of Zindiq would preach on the pulpit if the knowledge was not memorized by the sanad in the book. And a famous aphorism Imam Abdullah bin Mubarak says, sanad is a part of religion, if without sanad the people will say whatever they want. The aim of this research is to find out, analyze and interpret the scientific genealogy and nationalism attitude of KH. Zaini Mun'im and KHR. As'ad Syamsul Arifin. This research used qualitative research method with the phenomenology approach and interpretation. Based on the results of this research, it can be concluded that in terms of the scientific sanad, the two kiai have a sense of continuity between the ulama '(teacher) with one another, so that based on this scientific sanad it shows that the articulation of Islamic teaching is very accountable in the context of Islamic teaching and the institutional development process in both pesantren continues dynamically by doing the transition from traditional pesantren to modern pesantren. and based on the religious nationalism attitude, it can be concluded that both of them have high enthusiasm in their patriotism by carrying out a multicultural mission.